"Liaisons dangereuses": The invasive red‐vented bulbul (Pycnonotus cafer), a disperser of exotic plant species in New Caledonia. Issue 18 (24th August 2018) - Thibault, Martin; Masse, Felix; Pujapujane, Aurore; Lannuzel, Guillaume; Bordez, Laurent; Potter, Murray A.; Fogliani, Bruno; Vidal, Éric; Brescia, Fabrice
Abstract: The biodiversity hotspot of New Caledonia hosts high levels of endemism (74% of flora) that is threatened increasingly by climate change, habitat reduction, and invasive species. The fruit‐eating red‐vented bulbul ( Pycnonotus cafer ) is currently invading the main island of the archipelago, and its recent dispersal out of urbanized habitats raises questions about its potential to disperse noxious plant seeds along urban corridors and beyond. Indeed, the red‐vented bulbul is considered a vector of several introduced plant species in its alien range including Miconia calvescens, Lantana camara, and Schinus terebinthifolius . We conducted a quantitative assessment of the bulbul's fruits consumption by analyzing the gut contents of shot birds. We estimated gut passage times for four species of fruit found in gut contents ( S. terebinthifolius, Myrtastrum rufopunctatum, Passiflora suberosa, and Ficus prolixa ) and tested the effects of bird digestion on seed germination rates for two species. Finally, we monitored the movements of individual VHF radio‐tagged red‐vented bulbuls. All of the consumed fruit species we identified here have red fleshy diaspore, including fruit of the shrub M. rufopunctatum that occurred frequently (9.6%) in bulbul gut samples. Median gut passage times were short (15–41 min), corresponding to short‐distance seed transportation (77–92 m). The effect of gut passage was positive for the germination of the invasive S. terebinthifolius and negative for the endemic M. rufopunctatum, suggesting a potential bias in the contribution to the dispersal toward alien species. This study provides the first integrated assessment of mechanisms involved in the seed dispersal effectiveness of this high‐concern invasive bird species that is expected to face similar plant communities in most of its alien range in tropical islands. More generally, our results enhance knowledge of synergies between non‐native frugivores and plant species dispersal. Abstract : The unique flora of New Caledonia (78% endemism) is facing pressures from climate change, habitat loss, and invasive species including exotic fruit‐eating birds. We explored the potential consequences from the current dispersal of the red‐vented bulbul, beyond inhabited habitats where it is likely associated with a community of exotic plant species. Our findings confirm its contribution to the seed dispersal network and suggest a potential biased contribution to seeds dispersal in favor of exotic species compared to endemic ones.